Efficacy of anthelmintics against nematodes in naturally infected free range ducks - Ausraful Islam; Anisuzzaman; Shankar Majumder; Mohammad Atiqul Islam; Abul Kalam Mohammad Arifur Rabbi; Mohammad Hafezur Rahman (Eurasian Journal of Veterinary Sciences)
The objective of this study was to compare the efficacy of four anthelmintics (piperazine citrate, albendazole, fenbendazole, ivermectin) against nematodes of free range ducks. Twenty free-range ducks were selected from different farmer's house by fecal examination which was infected with three species of helminths. Ducks were divided into four treatment groups with five replications. Eggs per gram of faeces (epg) were calculated on pre-treatment and on day 7th, 14th, 21st and 30th post-treatment. All the anthelmintics showed 100% efficacy up to 14 days against all helminths except Amidostomum sp. Fenbendazole showed 100% efficacy against all nematodes except 67% against Capillaria sp. up to 21 days. Ivermectin showed 100% efficacy against all the helminths up to 21 days. Ducks treated with piperazine citrate, fenbendazole and ivermectin got the maximum protection against infection with Capillaria sp. In conclusion, it might be stated that piperazine citrate and ivermectin showed better efficacy than albendazole and fenbendazole.